Studies on anti-allergic constituents in the leaves and stems of Anchietia salutaris var. martiana (Violaceae) - Di Stasi, L. C.; Gomes, J. C.; Vilegas, Wagner [UNESP] (Pharmaceutical Soc Japan, 1999)
The anti-allergic active fractionation of hexane extracts of the leaves and stems of Anchietia salutaris,ar. martiana (family Violaceae) nas performed by monitoring their activities with an in vitro bioassay system measuring the inhibitory effects on induced histamine release from guinea pig lung cells. Three known pentacyclic triterpenes (friedelin, alpha-amyrin, beta-amyrin) were isolated, but these compounds were inactive. Aliphatic hydrocarbons and methyl esters of fatty acids (palmitic, oleic, linoleic, linolenic acids) were detected in active fractions. All compounds isolated were detected for the first time in this medicinal plant.
Keywords: Anchietia salutaris; anti-allergy; histamine release; fatty acids